2010
DOI: 10.1007/s11547-010-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiological findings of pneumonia in patients with swine-origin influenza A virus (H1N1)

Abstract: In our series, the most frequent pneumonia patterns observed during S-OIV (H1N1) virus were interstitial changes and patchy ground-glass appearance, mostly bilateral, and located in the lower lung zones. CT, performed in severely ill patients, confirmed the ARDS identified with chest X-rays, better depicting the features and extent of lung abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
4
15
1
1
Order By: Relevance
“…In addition to Aviram's early series, a number of further small studies of hospitalised H1N1 patients went on to demonstrate bilateral, 'patchy' and lower zone predominance as the dominant imaging findings [13][14][15][16][17], with some studies also supporting our findings of a predominantly peripheral distribution [6,11,[16][17][18][19]. Peripheral opacification on the chest X-ray is an atypical pattern for viral pneumonias [20] making this a useful defining and discriminatory feature.…”
Section: Length Of Stay Median Days (Iqr) P-valuesupporting
confidence: 59%
“…In addition to Aviram's early series, a number of further small studies of hospitalised H1N1 patients went on to demonstrate bilateral, 'patchy' and lower zone predominance as the dominant imaging findings [13][14][15][16][17], with some studies also supporting our findings of a predominantly peripheral distribution [6,11,[16][17][18][19]. Peripheral opacification on the chest X-ray is an atypical pattern for viral pneumonias [20] making this a useful defining and discriminatory feature.…”
Section: Length Of Stay Median Days (Iqr) P-valuesupporting
confidence: 59%
“…In a study, major radiological signs were reported as interstitial changes, ground glass opacities singly or together with interstitial changes, and consolidation; it was indicated that the involvement occurred particularly bilateral and in lower lobes. In the same study, ARDS signs were present in 7.5 % of the patients whilst pleural effusion attended in 10 % of the patients [2]. Similarly, the most commonly encountered signs in our study were interstitial changes, consolidation and ground glass opacities.…”
supporting
confidence: 80%
“…These signs vary and may manifest together. Symptoms of ARDS may develop in the patients, but pleural effusion is rare [2]. In a study, major radiological signs were reported as interstitial changes, ground glass opacities singly or together with interstitial changes, and consolidation; it was indicated that the involvement occurred particularly bilateral and in lower lobes.…”
mentioning
confidence: 99%
“…Aree multifocali di opacità degli spazi aerei possono diventare rapidamente confluenti sulle radiografie del torace di controllo e rappresentano all'imaging una combinazione di danno alveolare diffuso, di emorragia e di polmonite in organizzazione, eventualmente con sovrapposta infezione batterica secondaria nelle fasi avanzate della malattia [1,20,22]. Il versamento pleurico è spesso assente [23]. Ci sono state poche importanti casistiche pubblicate sull'H1N1.…”
Section: Un Nuovo Sottotipo DI Virus Influenzale a (H1n1) Si è Diffusounclassified